Extending the Developmental Interpretation of Delusions and Hallucinations.. - Glick, Marion (1988)
Keywords: dept.psy; faculty_collection; sabbatical_report

The Copts Since the Arab Invasion: Strangers in Their Land - Karas, Shawky F. (American, Canadian, and Australian C. Coptic Associations, 1985)
Keywords: 1952-1970; Copts; Egypt; Ethnic relations; Egypt; Politics and government; dept.psy

The Inquisitive Eye - Fineman, Mark B. (Oxford University Press, 1981)
Keywords: Problems; exercises; etc; Visual perception; Visual perception; dept.psy; faculty_collection

The Need to Test Hypotheses About Paranoid Schizophrenia: Reply to Clementz and Sweeney - Glick, M.; Zigler, E. (American Psychologist, 1989)
0 citations (Crossref) [2023-10-31]
Keywords: Depressive Disorder; Diagnosis; Differential; Human; Psychiatric Status Rating Scales; Schizophrenia; Paranoid; article; depression; dept.psy; differential diagnosis; human; paranoid schizophrenia; psychological aspect; rating scale

Preventing maladjustment from infancy through adolescence - rickel,au, allen,l - Glick, M (Contemporary Psychology, 1989)
0 citations (Crossref) [2023-10-31] tex.unique-id: ISI:A1989CE35400063
Keywords: dept.psy

Theories of probabilistic reinforcement. - Mazur, James E (Journal of the Experimental Analysis of Behavior, 1989)
In three experiments, pigeons chose between two alternatives that differed in the probability of reinforcement and the delay to reinforcement. A peck at a red key led to a delay of 5 s and then a possible reinforcer. A peck at a green key led to an adjusting delay and then a certain reinforcer. This delay was adjusted over trials so as to estimate an indifference point, or a duration at which the two alternatives were chosen about equally often. In Experiments 1 and 2, the intertrial interval was varied across conditions, and these variations had no systematic effects on choice. In Experiment 3, the stimuli that followed a choice of the red key differed across conditions. In some conditions, a red houselight was presented for 5 s after each choice of the red key. In other conditions, the red houselight was present on reinforced trials but not on nonreinforced trials. Subjects exhibited greater preference for the red key in the latter case. The results were used to evaluate four different theories of probabilistic reinforcement. The results were most consistent with the view that the value or effectiveness of a probabilistic reinforcer is determined by the total time per reinforcer spent in the presence of stimuli associated with the probabilistic alternative. According to this view, probabilistic reinforcers are analogous to reinforcers that are delivered after variable delays. 1989 Society for the Experimental Analysis of Behavior
72 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/098-819-689-500-794 tex.type: [object Object]
Keywords: Animal; Color Perception; Conditioning; Operant; Mental Recall; Probability Learning; Reinforcement Schedule; Support; U.S. Gov't; P.H.S.; adjusting schedule; animal; article; color vision; conditioned reinforcement; dept.psy; instrumental conditioning; intertrial interval; key peck; learning; pigeons; recall; reinforcement; reinforcer delay; reinforcer probability

The need to test hypotheses about paranoid schizophrenia: reply to Clementz and Sweeney. - Glick, Marion; Zigler, Edward (American Psychologist, 1989)
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/079-001-880-085-55X tex.type: [object Object]
Keywords: dept.psy

Depression: A failure to suppress the self-conscious ‘Monitoring’ of dismal cognitions - Kunzendorf, Robert G; Mclaughlin, Susan (Imagination, Cognition and Personality, 1989)
11 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/061-928-824-373-602 tex.type: [object Object]
Keywords: dept.psy

Is paranoid schizophrenia really camouflaged depression - Zigler, Edward; Glick, Marion (American Psychologist, 1988)
85 citations (Crossref) [2023-10-31] tex.type: Journal article
Keywords: dept.psy

Effect of lysine-8-vasopressin on retention and retrieval of a discrimination reward task in the rat. - Mulvey, Debra J; Watt, Jean M; Mcewen, Barbara B; Flannelly, Linda M (Behavioral Neuroscience, 1988)
The effect of vasopressin on memory of a brightness discrimination reward task was investigated in 20 male Sprague-Dawley rats. Two measures of retention were used: resistance to extinction and savings scores on a reacquisition task given 45 days after the completion of extinction training. The effect of the peptide on both memory consolidation and retrieval was assessed. There were two major findings: (a) The peptide enhanced memory consolidation of the task whether measured after a short time interval (6 days) or after a long time interval (45 days after completion of extinction training) using a measure of trials to relearn the task, and (b) the peptide had no effect on memory retrieval. These results were compared to those of other studies designed to access memory consolidation and retrieval on appetitive tasks. The mechanisms of the peptide's effect on memory was briefly discussed with respect to three theories on the subject. This study extends the vasopressin research on memory consolidation by suggesting that it pertains to appetitive as well as to aversive tasks.
5 citations (Crossref) [2023-10-31] tex.type: Journal article
Keywords: Animal; Appetitive Behavior; Brain; Conditioning; Operant; Discrimination Learning; Extinction (Psychology); Lypressin; Male; Memory; Mental Recall; Motivation; Orientation; Rats; Rats; Inbred Strains; Retention (Psychology); animal experiment; controlled study; dept.psy; lypressin; male; memory consolidation; memory retrieval; nonhuman; psychological aspect; psychophysiology; rat; reward

Premorbid competence, role orientation, and gender differences in DSM-II versus DSM-III schizophrenic patients. - Glick, Marion; Quinlan, Donald M; Zigler, Edward (Journal of Consulting and Clinical Psychology, 1987)
The study compared 71 patients diagnosed as schizophrenic or within the schizophrenia spectrum according to the second edition of the Diagnostic and Statistical Manual of Mental Disorders (DSM-II) with 66 patients who received similar diagnoses according to the third edition of the same manual (DSM-III). On measures of premorbid competence and role orientation, DSM-II and DSM-III schizophrenic patients obtained comparable scores. The DSM-III patients with schizophrenic versus schizophrenia spectrum diagnoses also obtained comparable scores on these measures. The gender differences in premorbid competence and role orientation that have consistently characterized DSM-II schizophrenics continued to characterize DSM-III schizophrenic and schizophrenia spectrum patients. The results suggest that findings previously obtained with DSM-II schizophrenics concerning premorbid competence and role orientation can be generalized to DSM-III schizophrenics. © 1987 American Psychological Association.
3 citations (Crossref) [2023-10-31] tex.type: Journal article
Keywords: adult; classification; competence; dept.psy; gender; human; major clinical study; orientation; schizophrenia

Effectiveness of the Mini-Mult in detecting MMPI pathology in the blind - Needham, Walter E.; Ehmer, Marjy N.; Marchesseault, Linda; l'Aune, William R. De (Journal of Clinical Psychology, 1986)
The Mini‐Mult and MMPI were administered in random order to 60 blind male veterans admitted to a residential rehabilitation program. Mini‐Mult scores predicted the presence or absence of MMPI pathology in 81.7% of the cases. Correlations between the individual Mini‐Mult and MMPI scales were significant at the p < .01 level, but not of sufficient magnitude to permit their interchangeability or to allow for profile diagnosis on the basis of Mini‐Mult scores. Analysis of the false negatives raises questions about the clinical significance of an abnormal MMPI in the population studied. The results support the value of the Mini‐Mult as a screening device, but not as a substitute for a detailed psychological assessment of the blind. Copyright © 1986 Wiley Periodicals, Inc., A Wiley Company
4 citations (Crossref) [2023-10-31] Citation Key Alias: pop00119 tex.type: [object Object]
Keywords: Blindness; Human; MMPI; Male; Mass Screening; Mental Disorders; Middle Age; adult; blindness; central nervous system; clinical article; dept.psy; human; priority journal; psychological aspect; rehabilitation; visual system

Premorbid social competence and psychiatric outcome in male and female nonschizophrenic patients - Glick, Marion; Zigler, Edward (Journal of Consulting and Clinical Psychology, 1986)
The relation between premorbid social competence and outcome was examined in 448 (228 male and 220 female) first-admission, nonschizophrenic, state-hospital patients. For both sexes, higher social competence was related to more favorable outcome as reflected in shorter initial hospitalizations and shorter rehospitalizations. Consistent with a developmental formulation, these results provide further evidence that the relation between premorbid competence and outcome is not unique to schizophrenia but can be found for patients of both sexes across a range of diagnoses. © 1986 American Psychological Association.
12 citations (Crossref) [2023-10-31] tex.type: Journal article
Keywords: adult; central nervous system; clinical article; competence; dept.psy; human; mental patient; psychological aspect; social aspect; social behavior; therapy

Young-children reinvent arithmetic - implications of piaget theory - kamii,ck, declark,g - Smith, JP (Teachers College Record, 1986)
tex.unique-id: ISI:A1986D941000011
Keywords: dept.psy; ⛔ No DOI found

Developmental correlates of age at first hospitalization in nonschizophrenic psychiatric patients - Glick, M.; Zigler, E.; Zigler, B. (Journal of Nervous and Mental Disease, 1985)
Age at first hospitalization, premorbid social competence, and developmental categorizations of symptomatology were examined in 228 male and 220 female patients in three diagnostic categories: Major affective disorder, neuroses, and personality disorder. High social competence patients were older at first hospitalization than low competence individuals. Younger first admission patients showed more symptoms in the action category and in the role orientation of turning against others. Older patients more frequently displayed symptoms of the thought variety and of turning against the self. Gender differences in age at first hospitalization were not found. With respect to all developmental variables examined, the results suggest that a broader view of prognosis proposed in research with schizophrenic patients is applicable to nonschizophrenic groups. © 1985 by The Williams & Wilkins Co.
15 citations (Crossref) [2023-10-31]
Keywords: Adult; Age Factors; Female; Hospitalization; Human; Male; Marriage; Mental Disorders; Middle Age; Mood Disorders; Neurotic Disorders; Occupations; Personality Disorders; Prognosis; Role; Sex Factors; Social Adjustment; Support; Non-U.S. Gov't; Support; U.S. Gov't; P.H.S.; affective neurosis; age; central nervous system; clinical article; dept.psy; hospitalization; human; mental patient; neurosis; personality disorder; priority journal; psychological aspect; social aspect; sociology

Paranoid schizophrenia: An unorthodox view. - Zigler, Edward; Glick, Marion (American Journal of Orthopsychiatry, 1984)
12 citations (Crossref) [2023-10-31] Citation Key Alias: ISI:A1984SB44900004 tex.eissn: [object Object] tex.unique-id: [object Object]
Keywords: dept.psy

Parent diary - a technique for sampling the expressive language of hearing-impaired children - Kessler, ME (Volta Review, 1983)
tex.unique-id: ISI:A1983QK55500004
Keywords: dept.psy; ⛔ No DOI found

Complexity of context and orientation of figure in the corridor illusion - Fineman, Mark B (Perceptual and Motor Skills, 1981)
10 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/007-837-285-081-691 tex.type: [object Object]
Keywords: dept.psy

Comparison of competitive trait anxiety levels of 9-12-year-old participants in little league and neighborhood baseball - Finn, JA; Sprague, LK (International Journal of Sport Psychology, 1981)
tex.unique-id: ISI:A1981ML28300017
Keywords: dept.psy; ⛔ No DOI found

Premorbid social competence and the revolving door phenomenon in psychiatric hospitalization - Marsh, A.; Glick, M.; Zigler, E. (Journal of Nervous and Mental Disease, 1981)
The relation between premorbid social competence and length of initial hospitalization was examined in 381 male state hospital patients in four diagnostic categories: Schizophrenic, affective reaction, psychoneurotic, and personality disorder. A significant relation was discovered between diagnosis and outcome, with schizophrenic patients having the longest and personality disorder patients the shortest lengths of initial hospitalization. Premorbid social competence was related to outcome, as assessed both by length of initial hospitalization, and by whether the patient was rehospitalized. These two outcome measures were found to be positively related, thus supporting the developmental formulation that premorbid social competence is indicative generally of prognosis. The findings were employed to generate the inference that patients at differing levels of premorbid social competence require different treatment modalities. © 1981 by The Williams & Wilkins Co.
8 citations (Crossref) [2023-10-31]
Keywords: Adult; Hospitals; Psychiatric; Human; Length of Stay; Male; Mental Disorders; Mood Disorders; Neurotic Disorders; Personality Disorders; Recurrence; Schizophrenia; Social Adjustment; central nervous system; dept.psy; major clinical study; mental hospital; personality disorder; schizophrenia; sociology

Inter-relationships among hospitalization measures of psychiatric outcome - Glick, M.; Marsh, A.; Zigler, E. (Journal of Nervous and Mental Disease, 1980)
In a diagnostically heterogeneous sample of 381 first admission male state hospital patients, no consistent correlations appeared among three commonly employed hospitalization measures of outcome. The possibility that psychiatric hospitalization may be a multidimensional criterion is considered and the implications for outcome research are discussed. © 1980 by The Williams & Wilkins Co.
3 citations (Crossref) [2023-10-31]
Keywords: Follow-Up Studies; Hospitalization; Human; Length of Stay; Male; Mental Disorders; Models; Theoretical; Patient Readmission; Support; U.S. Gov't; P.H.S.; central nervous system; dept.psy; hospitalization; major clinical study; therapy

Irrational thinking and adjustment to loss of vision - Needham, WE; Ehmer, MN (Journal of visual impairment & blindness, 1980)
11 citations (Crossref) [2023-10-31] tex.eissn: 1559-1476 tex.unique-id: ISI:A1980JK16600003
Keywords: dept.psy